Transforming Textile Waste into Educational Play Tools for Early Childhood: A Mentorship Program in Aceh Tengah - Samad, Munawwarah; Rahmi, Putri; Herawati, Herawati; Juwita, Rani Puspa (Jurusan PIAUD UIN Siber Syekh Nurjati Cirebon, 2025)
Through play activities, children demonstrate their stages of growth and development. However, Early Childhood Education often encounters challenges, such as funding issues. The high cost of educational play tools and the lack of knowledge among educators in designing and creating educational tools using available materials from the environment are significant obstacles. The goals of this research are to analyze the initial capabilities of ECE educators in Bebesen Subdistrict, Central Aceh, in understanding the basic concepts of making educational play tools before mentoring; to design convection waste-based educational tools for classroom units in Bebesen Subdistrict; and to describe the mentoring process in making educational play tools from convection waste. This activity involves ECE educators in Bebesen using a qualitative descriptive approach with data collection techniques including interviews, focus group discussions (FGD), and documentation. The outcome of the research includes educational play tools made from convection waste that can be used in learning activities. ECE educators successfully developed skills to create various types of educational tools from convection waste. Utilizing garment industry waste reduces environmental waste and lowers the cost of making educational tools, making the program environmentally friendly and sustainable.